2010
DOI: 10.1007/s00421-010-1614-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contrast water therapy duration on recovery of cycling performance: a dose–response study

Abstract: This study investigated whether contrast water therapy (CWT) has a dose-response effect on recovery from high-intensity cycling. Eleven trained male cyclists completed four trials, each commencing with a 75-min cycling protocol containing six sets of five 15-s sprints and three 5-min time-trials in thermoneutral conditions. Ten minutes post-exercise, participants performed one of four recovery protocols: CWT for 6 min (CWT6), 12 min (CWT12), or 18 min (CWT18) duration, or a seated rest control trial. The CWT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
6
45
2
1
Order By: Relevance
“…These Wndings are in accordance with previous research on recreational subjects utilising CWT (CoVey et al 2004;Versey et al 2010) or CWI (Stacey et al 2010) therapy following similar exercise intensities and/or bouts. To the best of the authors knowledge, no previous research uses a subject population of such international (elite) calibre, and accordingly, where the highly trained status of the subject population may predispose them to a faster recovery than untrained populations (Ravier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These Wndings are in accordance with previous research on recreational subjects utilising CWT (CoVey et al 2004;Versey et al 2010) or CWI (Stacey et al 2010) therapy following similar exercise intensities and/or bouts. To the best of the authors knowledge, no previous research uses a subject population of such international (elite) calibre, and accordingly, where the highly trained status of the subject population may predispose them to a faster recovery than untrained populations (Ravier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…To the best of the authors knowledge, no previous research uses a subject population of such international (elite) calibre, and accordingly, where the highly trained status of the subject population may predispose them to a faster recovery than untrained populations (Ravier et al 2006). Similar to previous studies (CoVey et al 2004;Versey et al 2010), the current Wndings highlight that CWT may promote the maintenance of performance during maximal exercise in the short term (<1 h) compared to passive recovery or other immersion therapies. While it must be noted that the change in performance between the groups was 28%, for elite athletic populations, such improvements may be beneWcial for continued training quality.…”
Section: Discussionsupporting
confidence: 81%
“…Compared with passive recovery, hydrotherapy interventions did not substantially influence performance during a 14-min cycling time trial several hours after a HIT session. This outcome contrasts with the findings of other authors, who have reported either better performance (Lane and Wenger 2004;Vaile et al 2008;Versey et al 2011) or poorer performance (Crowe et al 2007;Parouty et al 2010;Schniepp et al 2002) following hydrotherapy treatments. Among these studies, hydrotherapy improved performance during high-intensity cycling of 25-120 min in duration performed following 2 h (Versey et al 2011) or 24 h (Lane and Wenger 2004;Vaile et al 2008) of recovery.…”
Section: Discussioncontrasting
confidence: 86%
“…(1) 5 min of CWI is effective at reactivating cardiac parasympathetic activity (Al Parouty et al 2010), and lowering body temperature while remaining tolerable ), and (2) CWT of greater than 12 min does not provide any additional enhancement in subsequent exercise performance (Versey et al 2011). No specific information on the role or possible effects of each recovery intervention was provided to the athletes prior to the study to limit any bias in treatment response.…”
Section: Recovery Interventionsmentioning
confidence: 98%
See 1 more Smart Citation